COLORFUL TRENDS IN LIFE: रंगों का जीवन में रसात्मक रूझान - सुनीता (International Journal of Research -GRANTHAALAYAH, 2014)
The most appropriate place for rasa-nispti is theater, where the actor performs the rasa bhavas by enacting various gestures, and the observer, seeing his performance, is lost or drowned in the same sense for a moment. This feeling is called beauty. Although there is a diverse feeling of juice by different expressions. But this does not mean that the juice is divisible, but they are color-bleached forms of the same feeling. It is a symbol of nature's various juices. Happiness, sorrow, color and color are present according to different circumstances in life. For example, the color Shyam is a symbol of adornment. So the red color is the brown of the brave and the heroic juice is the manifestation of the compassionate juice, the black is the blue of the terrible, and the yellow is the strange color of the strange colors; Western art admirer Laurence Winian has also accepted "some types of colors are really brain." Has a real connection with the emotional conditions of the person. "According to Bharata, the ideal observer is the one who identifies with the emotion played in the Natya Shala and where is it." All is useless chanting, meditating, reciting mantras, chanting garlands, doing devotional devotion. , Unless one realizes the true significance of the colors, the real significance of the letters, the aura and the properties of the shapes. "Indian mystics have considered Rasa beauty and pleasure almost synonymous. Which is very important in life. रस-निस्पत्ति का सबसे उपयुक्त स्थान रंगमंच है, जहां अभिनेता विभिन्न भाव भंगिमाओं को अभिनित कर रस की भावों द्वारा निस्पत्ति करता है, और प्रेक्षक उसके अभिनय को देखकर पलभर के लिए उसी भाव में खो जाता है या डूव जाता है। यही अनुभूति सौन्दर्य अनुभूति कहलाती है। यद्यपि रस की विविध अनुभूति विभिन्न भावों द्वारा होती है। किन्तु इसका यह अर्थ नही है कि रस विभाज्य है, किन्तु वे एक ही अनुभूति के रंग विरंगे स्वरूप है। प्रकृति के विभिन्न रस के प्रतिक है। जीवन में खुशी, गम, विभिन्न परिस्थिति के अनुरूप रंग रस उपस्थित होता है। जैसे श्याम रंग श्रंगार का प्रतीक है। तो लाल रंग रौद्व और वीर रस का भूरा करूण रस का घोतक है तो काला भयानक का नीला वीभत्स का वर्ण है तो पीला अदभुत का रंगों के इस प्रतीकात्मक मर्म को पाश्चात्य कला मर्मज्ञ लारेन्स विनियन ने भी स्वीकारा है ‘‘कुछ प्रकार के रंग सचमुच मस्तिष्क की भावनात्मक स्थितियों से वास्तविक सम्बन्ध रखते है।‘‘भरत के मतानुसार आर्दश प्रेक्षक वही है जो नाट्य शाला में अभिनीत भाव के साथ तादात्म रखता है और कहां है ‘‘सब बेकार है जप, तप करना मंत्रों का पढना माला जपना, साधना भक्ति करना, जब तक कि कोई रंगों के वास्तविक मर्म को अक्षरों के वास्तविक महत्व को आभाओं को और आकृतियों के गुणों को नहीं जान लेता।‘‘भारतीय मनीषियों ने रस सौन्दर्य एंव आनंद को लगभग पर्याय माना है। जो जीवन में अति आवश्यक है।